The interaction between supervisor and trainee teacher in the context of video feedback a statistical analysis of qualitative data. Issue 1 (2nd January 2018) - Bocquillon, Marie; Derobertmasure, Antoine
Abstract: In French-speaking Belgium, trainee teachers are required to develop reflective practice; that is to say 'looking critically at one's own practices''. This article focuses on a training activity aimed at developing reflective practice: the video feedback session. This is an activity during which each trainee and a supervisor discuss a video recording of a lesson given by the trainee. This article explores the interaction between supervisor and trainee teacher. A statistical analysis of a preliminary qualitative thematic coding was conducted on 10 transcripts of video feedback sessions in order to study the thematic continuity of the discussion.